Measurement of the axial point spread function in scattering media using single-mode fiber-based optical coherence tomography - van Leeuwen, T.G.; Faber, D.J.; Aalders, M.C. (IEEE journal of selected topics in quantum electronics, 2003)
The authors studied the axial point spread function of optical coherence tomography for Gaussian intensity profiles emitted from and coupled back into single-mode fibers for signals from a scattering medium. The determined Rayleigh length of the axial point spread function was roughly twice the one measured from the reflection of a mirror. Using the measured point spread function in combination with the single backscatter model allowed determination of the attenuation coefficient of the suspension.